TC-PTP regulates the IL-7 transcriptional response during murine early T cell development. Issue 1 (December 2017) - Pike, K.; Hatzihristidis, T.; Bussières-Marmen, S.; Robert, F.; Desai, N.; Miranda-Saavedra, D.; Pelletier, J.; Tremblay, M.
Abstract Cytokines play a critical role in directing the discrete and gradual transcriptional changes that define T cell development. The interleukin-7 receptor (IL-7R), via its activation of the JAK-STAT pathway, promotes gene programs that change dynamically as cells progress through T cell differentiation. The molecular mechanism(s) directing differential gene expression downstream of the IL-7R are not fully elucidated. Here, we have identified T cell protein tyrosine phosphatase (TC-PTP), also known as PTPN2, as a negative regulator of IL-7R-STAT signaling in T cell progenitors, contributing to both the quantitative and qualitative nature of STAT-gene targeting. Novel genetic strategies used to modulate TC-PTP expression demonstrate that depletion of TC-PTP expression heightens the phosphorylation of STAT family members, causing aberrant expression of an interferon-response gene profile. Such molecular re-programming results in deregulation of early development checkpoints culminating in inefficient differentiation of CD4+ CD8+ double positive cells. TC-PTP is therefore shown to be required to safeguard the dynamic transcriptome necessary for efficient T cell differentiation.